2018
DOI: 10.1155/2018/3025185
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Cutaneous Leishmaniasis in Sri Lanka

Abstract: Cutaneous leishmaniasis (CL) is a neglected tropical disease which affects mainly the poorest communities in developing countries. Considering the limited published information on economic impact of CL in Sri Lanka, the current study was conducted with the objective of revealing the nature and magnitude of the economic impact of CL in three selected disease endemic regions in Kurunegala District, Sri Lanka. The patient records of CL notified of relevant Medical Officer of Health (MOH) office during 2013- 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Transport and food comprised the higher direct non-medical costs; expenses on food were associated with traveled distance for CL diagnosis, which is corroborated by prior studies, that reported an increase in CL expenses due to travel demand 8,14 . The low resolubility of the primary health care of the state of Minas Gerais in caring and managing patients with CL signs, verified by this study, may increase these expenses.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Transport and food comprised the higher direct non-medical costs; expenses on food were associated with traveled distance for CL diagnosis, which is corroborated by prior studies, that reported an increase in CL expenses due to travel demand 8,14 . The low resolubility of the primary health care of the state of Minas Gerais in caring and managing patients with CL signs, verified by this study, may increase these expenses.…”
Section: Discussionsupporting
confidence: 79%
“…The participants of this study reported no expenses with hospitalization and caregivers for themselves or their children. In this study, the median total cost with CL was USD 125.38, much higher than that found by an economic evaluation study conducted in Sri Lanka (USD 66.85) 8 . Considering Brazil minimum wage at the period of data collection, equivalent to USD 283.02 (BRL 908.05), CL average monthly cost of USD 133.80 (BRL 429.50) may represent a significant economic loss for patients.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In Sri Lanka, the first indigenous case was identified in 1992, which was of the cutaneous type [24]. At present, more than 2,000 cases have been identified from 2000 to 2009 and nearly 8,487 patients have been recorded during 2009-2016 representing at least one case from all 25 administrative districts [25]. In 2018, the caseload has been increased compared to the past years denoting cases from nonendemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Later in the period from 2009 to 2016, nearly 8487 cases were notified representing at least one case from all 25 districts of the country. Some districts had an increasing trend of the disease prevalence with more than 100 new cases each year [14,15]. Therefore, more attention was drawn toward diagnostic, treatment, and vector-related studies of leishmaniasis by the scientific community.…”
Section: Introductionmentioning
confidence: 99%